2017
DOI: 10.1037/bul0000110
|View full text |Cite
|
Sign up to set email alerts
|

Coping, emotion regulation, and psychopathology in childhood and adolescence: A meta-analysis and narrative review.

Abstract: In this meta-analytic and narrative review, we examine several overarching issues related to the study of coping, emotion regulation, and internalizing and externalizing symptoms of psychopathology in childhood and adolescence, including the conceptualization and measurement of these constructs. We report a quantitative meta-analysis of 212 studies (N = 80,850 participants) that measured the associations between coping and emotion regulation with symptoms of internalizing and externalizing psychopathology. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
733
8
31

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 903 publications
(901 citation statements)
references
References 385 publications
46
733
8
31
Order By: Relevance
“…Although this effect was only marginally significant and thus requires replication, it is consistent with prior research showing adverse effects of avoidant coping (Aldao, Nolen-Hoeksema, & Schweizer, 2010; Compas et al, 2017; Nicolotti et al, 2003; Sandler et al, 1994; Tu et al, 2016). These results suggest that high use of avoidant coping may be particularly detrimental for youth who are exposed to high levels of chronic conflict over time.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although this effect was only marginally significant and thus requires replication, it is consistent with prior research showing adverse effects of avoidant coping (Aldao, Nolen-Hoeksema, & Schweizer, 2010; Compas et al, 2017; Nicolotti et al, 2003; Sandler et al, 1994; Tu et al, 2016). These results suggest that high use of avoidant coping may be particularly detrimental for youth who are exposed to high levels of chronic conflict over time.…”
Section: Discussionsupporting
confidence: 87%
“…The most widely recognized model by Lazarus and Folkman (1987) distinguishes subtypes of coping based on whether one’s efforts are focused on regulating emotions that arise in reaction to the stressor (i.e., emotion-focused) or making a direct impact on the stressors itself (i.e., problem-focused). This typology has frequently been applied to the search for matching coping strategies to context, as emotion-focused strategies are often presumed to be adaptive in the face of uncontrollable stressors, whereas problem-focused strategies are seen as adaptive in situations in which the individual has the ability to exert control and modify the stressor itself (Compas, Banez, Malcarne, & Worsham, 1991; Compas et al, 2017; Kerig, 2001). More recently, Compas and colleagues advocated for distinguishing active (i.e., engagement) strategies according to the motivational goals underlying one’s coping efforts, namely primary control (those focused on changing the situation or the consequences of one’s reaction to the situation; e.g., problem solving, emotion regulation, hiding emotional expression) and secondary control (those focused on adapting to the situation; e.g., cognitive reappraisal, distraction, acceptance, positive thinking) (Compas et al, 2001; Connor-Smith, Compas, Wadsworth, Thomsen, & Saltzman, 2000).…”
Section: Effective Coping As a Protective Factor Against The Effectsmentioning
confidence: 99%
“…Risk for depression varies in part as a function of the strategies women use to pursue their goals while navigating around and through obstacles in their internal and external environments. Coping and emotion regulation (ER) processes are used to initiate, delay, terminate, modify the form or content, or modulate the amount or intensity of a person's cognitive, emotional, behavioral, or physiological reactions to obstacles to goal attainment . They include many of the same strategies, but it is rare for both to be measured in the same study.…”
Section: Nih Model Stage 1a: Identifying Scientific Findings Relevantmentioning
confidence: 99%
“…In a meta‐analysis examining the impact of coping on 80,850 youth outcomes across 212 studies, Compas, Jaser, et al. () and Compas, Gruhn, et al. () found that engagement coping behaviors were associated with lower internalizing symptoms and usage of disengagement coping behaviors was associated with higher internalizing and externalizing symptoms.…”
Section: Adolescent Stress and Coping Behaviorsmentioning
confidence: 99%